2017
DOI: 10.1016/j.cdtm.2017.09.003
|View full text |Cite
|
Sign up to set email alerts
|

Intracranial artery stenosis: Current status of evaluation and treatment in China

Abstract: Intracranial artery stenosis (ICAS), a common cause of ischemic stroke, is a growing cause of concern in China. Recently, many epidemiological, etiological, pathophysiological, therapy, and diagnostic imaging studies have focused on ICAS, and guidelines and consensus on the diagnosis and treatment of ICAS have been published and updated by domestic experts. Such work is pivotal to our enhanced comprehension, diagnosis, and treatment of ICAS. In this review, we summarize the latest progress in the evaluation an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 94 publications
0
4
0
1
Order By: Relevance
“…Stenosis tends to cause vasodilation, which reduces cerebrovascular reactivity and at the same time, reduces the effectiveness of autoregulation. Conventional theory suggests that hemodynamic disturbances result from repeated episodes of hypotension due to severe arterial stenosis or occlusion [7] .…”
Section: Discussionmentioning
confidence: 99%
“…Stenosis tends to cause vasodilation, which reduces cerebrovascular reactivity and at the same time, reduces the effectiveness of autoregulation. Conventional theory suggests that hemodynamic disturbances result from repeated episodes of hypotension due to severe arterial stenosis or occlusion [7] .…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have shown that vascular risk factors, including high blood pressure, diabetes, hyperlipidemia, family history of stroke and heart disease, smoking, alcoholism, hyperhomocysteinemia, and being overweight, are associated with ICAS [4]. High blood pressure is one of the important risk factors for intracranial small vessel disease.…”
Section: Clinical Risk Factorsmentioning
confidence: 99%
“…In clinical practice, ischemic stroke can be caused by a variety of reasons. On the one hand, extracranial atherosclerotic disease (ECAD), which is dominated by carotid artery stenosis, accounts for about 18%25% of ischemic stroke [3].Another common cause of ischemic stroke is intracranial artery stenosis(ICAS) [4],that is, the artery stenosis caused by intracranial artery lesions, including atherosclerosis, aneurysm, arteritis, artery dissection, moyamoya disease and so on. Therefore, the diagnosis of intracranial artery disease is very important.…”
Section: Introductionmentioning
confidence: 99%
“…Akan tetapi, tekanan darah yang dipertahankan tinggi akan meningkatkan resiko kematian dan kecacatan. Studi yang dilakukan oleh Hao dkk menyatakan bahwa pasien stenosis arteri intrakranial dengan nilai tekanan darah sistolik lebih dari 160 mmHg ataupun kurang dari 120 mmHg akan memiliki resiko kematian dan kecacatan yang lebih tinggi, dibandingkan pada pasien dengan nilai tekanan darah sistolik antara 120-159 mmHg yang memiliki resiko outcome klinis buruk yang lebih rendah (18,19,20) .…”
Section: Hasil Dan Pembahasanunclassified